2020
DOI: 10.3348/kjr.2019.0755
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic Indeterminate Lymph Nodes in Preoperative Thyroid Cancer Patients: Malignancy Risk and Ultrasonographic Findings Predictive of Malignancy

Abstract: Proper management of lymph nodes (LNs) with ultrasonographic (US) indeterminate features in thyroid cancer patients remains elusive. We aimed to evaluate the malignancy risk and US findings predictive of malignancy for US indeterminate LNs in preoperative thyroid cancer patients through node-by-node correlation. Materials and Methods: A total of 348 LNs in 284 thyroid cancer patients, who underwent fine-needle aspiration or coreneedle biopsy between December 2006 and June 2015, were included. We determined the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…In contrast, various benign conditions occurring along with LNs and persistent inflammatory stimuli can cause unusual morphological changes in the nodal shape in the neck, and this can result in a false positive presentation of US-indeterminate LNs with deformed or displaced hilum [ 27 ]. For this reason, indeterminate LNs are often encountered during routine practice [ 14 ], and this frequent manifestation of indeterminate LNs limits the accuracy of US, even with the application of the size criteria [ 11 , 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, various benign conditions occurring along with LNs and persistent inflammatory stimuli can cause unusual morphological changes in the nodal shape in the neck, and this can result in a false positive presentation of US-indeterminate LNs with deformed or displaced hilum [ 27 ]. For this reason, indeterminate LNs are often encountered during routine practice [ 14 ], and this frequent manifestation of indeterminate LNs limits the accuracy of US, even with the application of the size criteria [ 11 , 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeterminate LNs are defined as LNs with no imaging findings of suspicious or benign LNs [ 13 ]. A recently published study showed the frequent occurrence of US-indeterminate LNs (23.6% among biopsied LNs in thyroid cancer patients), and demonstrated that the indeterminate category had a higher malignancy risk (19.5%) than the probably benign category (2.8%) [ 14 ]. Suspicious US features on conventional US showed high specificity and predictivity for diagnosing metastatic PTC [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hilar or central vascularity of the lymph node is a typical finding of a benign lymph node. In contrast, peripheral or diffuse vascularity is a US characteristic of lymph nodes with metastasis from thyroid cancer, and the absence of central hilar vascularity is a US criterion for an indeterminate lymph node [8,62]. Leboulleux et al [63] prospectively evaluated the diagnostic accuracy of US for lymph node metastasis in 56 lymph nodes from 19 patients with differentiated thyroid cancer.…”
Section: Diagnosis Of Metastatic Cervical Lymph Nodes In Patients Witmentioning
confidence: 99%
“…Hypoenhancement and heterogeneous enhancement on CEUS may be major features of malignant thyroid nodules [44][45][46][47][48][49]. Peripheral vascularity on Doppler US is a major finding for diagnosing metastatic cervical lymph nodes in patients with thyroid cancer [8,62]. Although many studies have reported that Doppler US is useful for the differentiation of thyroid nodules, few studies have evaluated the added value of Doppler US over gray-scale US for the differentiation of thyroid nodules [55].…”
Section: Summary Consensus and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation